Cultural Contents in The Textbook “English in Mind” In Relation to Sasak Lombok Culture - Fadia Citra Sabrina; Lalu Nurtaat; Kurniawan Apgrianto; Henny Soepriyanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Textbook is used as a tool to guide the teaching and learning process, provide and review material, sources of information, and knowledge about a subject. This study dealt with analysis of cultural contents in the textbook and the relation with the Sasak Lombok Culture. The purpose of this study was to identify the cultural contents presented in the textbook. This study was a qualitative descriptive study. The method of this study was content analysis. The data source for this research is the english textbook “English in Mind: Student’s Book 3” published by Cambridge University Press written by Herbert Puchta and Jeff Strank in 2010. The textbook analysis in this study considered 3 characteristics from Cortazzi and Jin (1999), namely: 1) Source Culture; 2) Target Culture; 3) International Culture; and one more added by Aliakbari (2004) which is 4) Neutral Culture. The results of the study showed that the textbook fulfills 3 characteristics, there were Target Culture, International Culture and Neutral Culture. From the analysis, there are 23 reading passages in the textbook, 10 reading texts are categorized as texts with target culture, 6 reading texts as texts with international culture and 3 reading texts as texts with neutral culture that has a relation with Indonesian culture in general including the Sasak Lombok Culture.